Explosion characteristic of stoichiometric syngas/air premixed gas in the flow state. Issue 1 (June 2021) - Wang, Baishi; Guo, Pinkun; Wang, Zhirong; Wang, Xuxu; Liu, Songjie; Xu, Chuanqing; Chang, Xinyue; Cao, Xingyan; Wang, Wei
Abstract: With increasing attention to energy efficiency and environmental protection, syngas has attracted great interest as a clean fuel with broad development prospects. In order to further study the effect of the initial gas flow on the explosion of syngas, an explosion experiment of stoichiometric syngas/air premixed gas was carried out in a 3 × 3 × 100 cm square explosion pipe. The composition of the syngas used in the experiment is 50CO:50H2, the flow rate of the experiment gas is 0L/min-250L/min, and the Reynolds number (Re) is 0-9598.41. The experimental results show that the maximum explosion pressure Pmax and the maximum explosion pressure rise rate (dp/dt)max gradually increase with the increase of the initial flow rate and Re. The gas flow increases the flame area, and increase the combustion rate, thereby making the explosion more violent.